Are sanitation interventions a threat to drinking water supplies in rural India? An application of tryptophan-like fluorescence. (1st January 2016) - Sorensen, J.P.R.; Sadhu, A.; Sampath, G.; Sugden, S.; Dutta Gupta, S.; Lapworth, D.J.; Marchant, B.P.; Pedley, S.
Abstract: Open defecation is practised by over 600 million people in India and there is a strong political drive to eliminate this through the provision of on-site sanitation in rural areas. However, there are concerns that the subsequent leaching of excreta from subsurface storage could be adversely impacting underlying groundwater resources upon which rural populations are almost completely dependent for domestic water supply. We investigated this link in four villages undergoing sanitary interventions in Bihar State, India. A total of 150 supplies were sampled for thermotolerant (faecal) coliforms (TTC) and tryptophan-like fluorescence (TLF): an emerging real-time indicator of faecal contamination. Sanitary risk inspections were also performed at all sites, including whether a supply was located within 10 m of a toilet, the recommended minimum separation. Overall, 18% of water supplies contained TTCs, 91% of which were located within 10 m of a toilet, 58% had TLF above detection limit, and sanitary risk scores were high. Statistical analysis demonstrated TLF was an effective indicator of TTC presence-absence, with a possibility of TTCs only where TLF exceeded 0.4 μg/L dissolved tryptophan. Analysis also indicated proximity to a toilet was the only significant sanitary risk factor predicting TTC presence-absence and the most significant predictor of TLF. Faecal contamination was considered a result of individual water supply vulnerability rather than indicative of widespread leaching into the aquifer. Therefore, increasing faecal contamination of groundwater-derived potable supplies is inevitable across the country as uptake of on-site sanitation intensifies. Communities need to be aware of this link and implement suitable decentralised low-cost treatment of water prior to consumption and improve the construction and protection of new supplies. Graphical abstract: Highlights: Sanitary interventions are a threat to groundwater-derived domestic supplies. Faecal contamination is a result of supply vulnerability. A lateral toilet-handpump separation of 10 m reduces the risk of contamination. Individuals need to employ simple point-of-use treatment technologies. Tryptophan-like fluorescence is widely effective to detect thermotolerant coliforms.